Enhancing responsiveness of human jejunal enteroids to host and microbial stimuli. (13th June 2020) - Ruan, Wenly; Engevik, Melinda A.; Chang‐Graham, Alexandra L.; Danhof, Heather A.; Goodwin, Annie; Engevik, Kristen A.; Shi, Zhongcheng; Hall, Anne; Rienzi, Sara C. Di; Venable, Susan; Britton, Robert A.; Hyser, Joseph; et al.
Abstract : Key points: Enteroids are a physiologically relevant model to examine the human intestine and its functions. Previously, the measurable cytokine response of human intestinal enteroids has been limited following exposure to host or microbial pro‐inflammatory stimuli. Modifications to enteroid culture conditions facilitated robust human cytokine responses to pro‐inflammatory stimuli. This new human enteroid culture methodology refines the ability to study microbiome:human intestinal epithelium interactions in the laboratory. Abstract: The intestinal epithelium is the primary interface between the host, the gut microbiome and its external environment. Since the intestinal epithelium contributes to innate immunity as a first line of defence, understanding how the epithelium responds to microbial and host stimuli is an important consideration in promoting homeostasis. Human intestinal enteroids (HIEs) are primary epithelial cell cultures that can provide insights into the biology of the intestinal epithelium and innate immune responses. One potential limitation of using HIEs for innate immune studies is the relative lack of responsiveness to factors that stimulate epithelial cytokine production. We report technical refinements, including removal of extracellular antioxidants, to facilitate enhanced cytokine responses in HIEs. Using this new method, we demonstrate that HIEs have distinct cytokine profiles in response to pro‐inflammatory stimuli derived from host and microbial sources. Overall, we found that host‐derived cytokines tumour necrosis factor and interleukin‐1α stimulated reactive oxygen species and a large repertoire of cytokines. In contrast, microbial lipopolysaccharide, lipoteichoic acid and flagellin stimulated a limited number of cytokines and histamine did not stimulate the release of any cytokines. Importantly, HIE‐secreted cytokines were functionally active, as denoted by the ability of human blood‐derived neutrophil to migrate towards HIE supernatant containing interleukin‐8. These findings establish that the immune responsiveness of HIEs depends on medium composition and stimuli. By refining the experimental culture medium and creating an environment conducive to epithelial cytokine responses by human enteroids, HIEs can facilitate exploration of many experimental questions pertaining to the role of the intestinal epithelium in innate immunity. Key points: Enteroids are a physiologically relevant model to examine the human intestine and its functions. Previously, the measurable cytokine response of human intestinal enteroids has been limited following exposure to host or microbial pro‐inflammatory stimuli. Modifications to enteroid culture conditions facilitated robust human cytokine responses to pro‐inflammatory stimuli. This new human enteroid culture methodology refines the ability to study microbiome:human intestinal epithelium interactions in the laboratory.